2016
DOI: 10.1155/2016/9343460
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Related DNA Damage and Cancer Stem Cell Markers in Nasopharyngeal Carcinoma

Abstract: Nitrative and oxidative DNA damage plays an important role in inflammation-related carcinogenesis. To investigate the involvement of stem cells in Epstein-Barr virus infection-related nasopharyngeal carcinoma (NPC), we used double immunofluorescence staining to examine several cancer stem/progenitor cell markers (CD44v6, CD24, and ALDH1A1) in NPC tissues and NPC cell lines. We also measured 8-nitroguanine formation as an indicator of inflammation-related DNA lesions. The staining intensity of 8-nitroguanine wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Western blot was done according to the standard protocol as described previously [ 31 ]. Cultured cells were harvested at 70-80% confluence and lysed using RIPA buffer (Cell Signaling Technology Inc., Dancers, MA, USA) supplemented PMSF (Phenylmethylsulfonyl fluoride, NACALAI TESQUE, INC., Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot was done according to the standard protocol as described previously [ 31 ]. Cultured cells were harvested at 70-80% confluence and lysed using RIPA buffer (Cell Signaling Technology Inc., Dancers, MA, USA) supplemented PMSF (Phenylmethylsulfonyl fluoride, NACALAI TESQUE, INC., Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Nasopharyngeal carcinoma is a human epithelial tumor with a high prevalence in Southeast Asia and Southern China and has a strong association with EB virus infection [ 11 , 26 ]. We examined stemness markers (CD44v6, ALDH1A1, CD24) in human nasopharyngeal carcinoma tissues [ 27 ]. IHC staining of CD44v6 and ALDH1A1 was observed in cancer tissues, but that of CD24 was not.…”
Section: Oxidative and Nitrative Damage Of Biomacromolecules In Inflamentioning
confidence: 99%
“…TAM‐secreted TNF‐α trigger chromosomal instability and enhance the self‐renewal of liver progenitor cells (Li, Chen, et al, ) (Figure ). Wang et al () measured 8‐Nitroguanine formation in NPC samples, which serve as a indicator of inflammation‐related DNA lesions. They observed that high level of 8‐Nitroguanine was detected in both CD44v6‐ and ALDH1A1‐positive stem cells in NPC tissues.…”
Section: Nf‐κb Stimulated Chronic Inflammation Promotes Cancer Stem Cmentioning
confidence: 99%